A Comparative Study of Educational Achievement Assessment System of Syria's Primary Schools with Iran - Afraa Arfi; Behrooz Mahram; Reem Slemon; Morteza Karami (Comparative Education Society of Iran ( CESIR), 2021)
The aim of present study was a comparative study of educational achievement assessment system of primary schools in Syria and Iran. For data collection, curriculum document analysis and semi-structured interviews with primary school teachers were used. Participants included 15 primary school teachers in both countries. The data obtained from the interview were analyzed using MAXQDA software. The results showed that assessment system of academic achievement in primary schools of Iran is qualitative-descriptive; whereas In Syria, it is quantitative, and pupils must obtain required scores to be promoted to a higher grade. Iranian students are interested in participating in qualitative assessment and this method has reduced their stress and anxiety. Conversely, Syrian students experience anxiety, fear, stress, and lack of self-confidence, and most feel disgusted with quantitative assessment system of academic achievement. The recommendation of study is reconsideration of assessment system - based on the goals of educational system and philosophical and psychological foundations - in Syria. It is also recommended to deepen and develop descriptive evaluation in Iran.